The Lack of Enforcement of the DRM Policy - Oliver, Stefanus; Winarta, Tommy (Swiss German University, 2020)
In this digital era, numerous copyrighted items such as music and movies can be enjoyed online. However, our activities in enjoying those entertainments are also limited by the copyright law. Some contents are also protected by Digital Rights Management, which makes sure that the user who purchases the item is the only person who has the right to enjoy the content. All of these rules are obviously made to make sure that everything is in order. Therefore, those illegal activities can be brought to justice. However, the lack of communication might present an ambiguity to the users, and those users might unconsciously do illegal things that are previously forbidden. Other than that, the law itself has its own limitation in the aspect of execution and enforcement, causing pirated versions of a content can be found easily on the internet. This paper is going to review the current condition of the execution of the law regarding the DRM protected contents.